FROM CLICK TO PURCHASE: EXPLORING THE INFLUENCE OF DIGITAL MARKETING ON REPURCHASE INTENTION THROUGH ELECTRONIC WORD OF MOUTH MARKETING IN MSMES - Yuliana, Rahmi; Hamdani, Muliawan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study addresses the inconsistency in research findings regarding the influence of digital marketing on repurchase intention, particularly for MSME products sold online. The research uses a quantitative approach with a positivist methodology and a conceptual model that requires empirical validation. Data was collected through a questionnaire distributed to 300 MSME consumers in Central Java, a region selected for its high repurchase intention for online MSME products. The findings show that while digital marketing does not directly and significantly influence repurchase intention, it has a strong, positive, and significant effect on electronic word of mouth marketing (eWOM). The study reveals that the impact of digital marketing on repurchase intention is only significant when it is mediated by electronic relationship marketing (ERM). This means that digital marketing's effectiveness in driving repeat purchases depends on its ability to first build trust, foster emotional connections, and create customer loyalty through digital platforms. The research concludes that for long-term success, businesses should focus on digital marketing strategies that nurture and develop customer relationships after the initial sale, rather than solely on attracting consumers for a first-time purchase.